Reliability of marginal microleakage assessment by visual and digital methods - Alvarenga, Fábio Augusto de Santi [UNESP]; Pinelli, Camila [UNESP]; Loffredo, Leonor de Castro Monteiro [UNESP] (Thieme, 2015)
The aim of this study was to investigate the reliability of visual and digital methods to assess marginal microleakage in vitro. Materials and Methods: Typical Class V preparations were made in bovine teeth and filled with composite resin. After dye penetration (0.5% basic fuchsin), teeth were sectioned and the 53 obtained fragments were assessed according to visual (stereomicroscope) and digital methods (Image Tool Software ® -ITS) (University of Texas Health Science Center-San Antonio Dental School, USA). Two calibrated examiners (A and B) evaluated dye penetration, by means of a stereomicroscope with ×20 magnification (scores), and by the ITS (millimeters). The intra- and inter-examiner agreement was estimated according to Kappa statistics (κ), and intraclass correlation coefficient (ρ). Results: In relation to the visual method, the intra-examiner agreement was almost perfect (κA = 0.87) and substantial (κB = 0.76), respectively to the examiner A and B. The inter-examiner agreement showed an almost perfect reliability (κ = 0.84). For the digital method, the intra-examiner agreement was almost perfect for both examiners and equal to ρ = 0.99, and so was the inter-examiner agreement value. Conclusion: Visual (stereomicroscope) and digital methods (ITS) showed high levels of intra- and inter-examiner reproducibility when marginal microleakage was assessed.
Keywords: Assessment; Composite resin; Microleakage; Reproducibility of results